Pendidikan Kepesantrenan dalam Perspektif Progresivisme John Dewey - Rahmatullah, Muhammad (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2015)
This paper discusses Islamic boarding schools from educational progressivism.Islamic boarding school is one typical and traditional education in Indonesia.This kind of education is considered no longer relevant in the modern world.Islamic boarding schools are freer and more open compared to formal education.Therefore, this kind of education tends to be more progressivism as proposedby John Dewey. Dewey requires that education must involve students directlywith investigation and experimentation. The material is taught to be somethingpractical in life. In addition, the school must be democratic so that it reflects thesocial system represented the school. From the writer’s observation, it was foundthat the preconditions of Islamic boarding schools meet progresissvisme.Kata Kunci: Education, Islamic boarding schools, Progressivism, John Dewey.